2020
DOI: 10.1055/a-1177-0849
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Increases in Resting Muscle Oxygen Consumption after a Women’s Soccer Match

Abstract: AbstractCurrently, near infrared spectroscopy has a clear potential to explain the mechanisms of fatigue by assessing muscle oxygenation. The objective of the study was to observe the changes in muscle oxygen consumption after an official women’s soccer match. The sample was 14 players who competing in the second division of Spain of women’s soccer. They were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…This percentage is similar to those reported in a recent systemic review of the representativeness of women in thermoregulation research, in which less than 30% of articles that included women reported their menstrual orientations (e.g., natural menstruating, hormonal contraceptive user, pregnant, and postmenopausal) and only 22% reported both menstrual orientation and phase [ 73 ]. Among the studies investigating female soccer, Bonilla et al [ 36 ] and Broodryk et al [ 37 ] evaluated the players only during the follicular phase to avoid variations in the data due to the menstrual cycle. Controlling for the menstrual cycle is relevant considering that CRP is increased in the early follicular phase [ 74 ], while reports of higher cortisol during the luteal phase also exist [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This percentage is similar to those reported in a recent systemic review of the representativeness of women in thermoregulation research, in which less than 30% of articles that included women reported their menstrual orientations (e.g., natural menstruating, hormonal contraceptive user, pregnant, and postmenopausal) and only 22% reported both menstrual orientation and phase [ 73 ]. Among the studies investigating female soccer, Bonilla et al [ 36 ] and Broodryk et al [ 37 ] evaluated the players only during the follicular phase to avoid variations in the data due to the menstrual cycle. Controlling for the menstrual cycle is relevant considering that CRP is increased in the early follicular phase [ 74 ], while reports of higher cortisol during the luteal phase also exist [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…s −1 ) Match 1—Active group 102 ± 21 93 ± 25* Missing Missing Missing 101 ± 21 Match 1—Passive group 104 ± 21 95 ± 21* Missing Missing Missing 104 ± 21 Match 2—Active group 101 ± 21 96 ± 11 Match 2—Passive group 104 ± 21 98 ± 12 Peak torque extension (°. s −1 ) Match 1—Active group 175 ± 21 165 ± 25* Missing Missing Missing 170 ± 25 Match 1—Passive group 167 ± 16 154 ± 21* Missing Missing Missing 160 ± 25 Match 2—Active group 170 ± 25 166 ± 14 Match 2—Passive group 160 ± 25 154 ± 21 Bonilla et al [ 36 ] CMJ height (cm) …”
Section: Meta-analysesmentioning
confidence: 99%
“…The device is considered valid for application in sports performance analysis (McManus et al, 2018). Furthermore, evaluating the SmO 2 variables at rest with AOM is an alternative method to finding the true muscle oxygen consumption at rest (Bonilla, et al, 2020).…”
Section: Assessment Muscle Oxygen Saturation At Restmentioning
confidence: 99%
“…Also, the difference between SmO ). These variables are widely described in the studies by Aldo Vasquez and Southern (Bonilla et al, 2020;Southern et al, 2014). All the variables were taken for the dominant leg (DL) and the nondominant (Non-DL) of each player in order.…”
Section: Assessment Muscle Oxygen Saturation At Restmentioning
confidence: 99%
“…La normalidad de la distribución de datos se verificó mediante la prueba de Kolmogorov-Smirnov (Maureira, 2017). Para verificar la existencia de una correlación bivariada entre el CMJ y la velocidad (10-30 m) y agilidad, se utilizará el estadístico de Pearson, para lo cual se adaptaron los siguien-tes criterios ya sean positivos o negativos para interpretar la magnitud de la correlación (r) entre las medidas de prueba: <0.1 trivial, 0.1-0.3 pequeño, 0.3-0.5 moderado, 0.5-0.7 grande, 0.7-0.9 muy grande y 0.9-1.0, casi perfecto (Bonilla et al, 2020). Finalmente, se realizó una regresión lineal simple para determinar el coeficiente de determinación (r 2 ) entre el CMJ y la velocidad (10-30 m) y agilidad (Little & Williams, 2005;Maly et al, 2014).…”
Section: Análisis Estadísticosunclassified